Regulating cryptocurrencies in South Africa - De Kock, William Chandler (School of Economics, 2022)
Cryptocurrencies are one of the most exciting financial technologies that have emerged since the global financial crisis. It has spurred on a new financial ecosystem looking to enhance the traditional financial system. Many of the economic functions such as payments, investment, trading and capital raising have made it to the cryptocurrency industry. Regulators, who have not universally agreed on how to approach regulating cryptocurrency activity, are seeking the best approaches to ensuring financial stability. This paper looks at the risk posed by cryptocurrencies and how to regulate the activities. It applies this directly to the South African context and finds that cryptocurrency activities are easily accommodated within the South African regulatory framework with a set of minor definition changes.